SCREENING OF CHICKPEA GENOTYPES AGAINST DRY ROOT ROT CAUSED BY MACROPHOMINA PHASEOLINA (TASSI) GOID - GOWDRA NAGAMMA,; MUHAMMAD SAIFULLA,; JABBAR SAB,; S. PAVITRA, (The Bioscan, 2015)
In the present study, Chickpea entries were screened against dry root rot disease in sick plot maintained at All India Co-ordinated Research project on chickpea, Bengaluru during Rabi, 2011-12. Only thirteen entries viz., GNG 1958 (AVT-2), GNG 1999, CSJ 303, BG 3004, CSJ 753, RSG 888, Phule G 04305, IPCK 07-62, RVSSG 12, HK 08-212, Phule G 09305, AKG 2002-1K and ICCV 08317 showed resistant reactions under field condition. The dry root rot fungus has a wide host range can infect several crops. It is difficult to manage by chemicals. Management can be made feasible and cost effective by identification of new resistant sources that is the only alternative method. Investigation attempt has been made to find out the resistance sources for dry root rot will be useful for control disease in future.